Impacto do acompanhamento farmacoterapêutico à pessoa com tuberculose na atenção primária à saúde na capital de Minas Gerais. - Célio Rezende Lara Júnior (2021)
Tuberculosis is an infectious disease of great relevance worldwide, which mainly affects the lungs and is responsible for 1.5 million deaths in the world population. According to the Brazilian Ministry of Health, in 2018, Brazil presented a rate of abandonment of tuberculosis treatment twice as high as the maximum recommended by the World Health Organization. Due to the magnitude of this problem, actions related to clinical practices, service organizations, and multidisciplinary interventions to tuberculosis control are encouraged by the national agenda of health research priorities. In this context, the role of the pharmacist is understood as an alternative that can improve the treatment of tuberculosis cases and positively impact the control of the disease in the country. Pharmacotherapeutic follow up is able to establish a bond with the patient, avoid problems related to the medication and assist in promoting a cure. Primary care is characterized as the main place of diagnosis and monitoring of tuberculosis. Since 2018, in the city of Belo Horizonte there has been the presence of pharmacists working in the care of patients with tuberculosis in all basic health units in an institutionalized way. Therefore, a study is proposed with the objective of evaluating the clinical impact of pharmaceutical care for tuberculosis patients in the city of Belo Horizonte and describing the implementation of this service in the municipality's care network. The data were obtained through the pharmaceutical assistance management software (GERAF) and searched in available medical records and they were statistically treated by Poisson regression with the aid of the Stata® software. The pharmaceutical service was realized in 148 primary health centers by 82 pharmacists between 2018 and 2020. In 721 treatments, there were 1709 appointments and the risk of relative cure due to the number of drugs used by the patient in addition to the anti-tuberculosis medication was 2.71 (2.04-3.61; p <0.001) times higher in the treatment group followed by the pharmacist. It is concluded that pharmaceutical care for tuberculosis patients has a significant clinical impact on the cure rate of patients and should be encouraged, as it is a viable, important, and easy to implement alternative in primary health care.